Вы находитесь на странице: 1из 11

# Aims Tutorial MATHEMATICS-IIB

Definite integrals
𝟏 𝐥𝐨𝐠(𝟏+𝒙)
𝝅/𝟒 𝒔𝒊𝒏𝒙+𝒄𝒐𝒔𝒙
2. ∫𝟎 (𝟏+𝒙𝟐 )
𝒅𝒙
1. ∫𝟎 𝟗+𝟏𝟔𝒔𝒊𝒏𝟐𝒙
𝒅𝒙

## 𝑠𝑜𝑙: 𝑙𝑒𝑡 𝒙 = 𝒕𝒂𝒏𝜽

𝑠𝑜𝑙: 𝑙𝑒𝑡 𝒔𝒊𝒏𝒙 − 𝒄𝒐𝒔𝒙 = 𝒕
𝑑𝑖𝑓𝑓 . 𝑤. 𝑟. 𝑡 ′𝑥 ′
𝑑𝑖𝑓𝑓 . 𝑤. 𝑟. 𝑡 ′𝑥 ′
𝒅𝒙 = 𝒔𝒆𝒄𝟐 𝜽𝒅𝜽
(𝒄𝒐𝒔𝒙 + 𝒔𝒊𝒏𝒙)𝒅𝒙 = 𝒅𝒕

𝐿. 𝐿: 𝑥 = 0 ⇨ 𝑡 = 𝑠𝑖𝑛𝑜 − 𝑐𝑜𝑠𝑜 = 0 − 1 = −1
𝜋 𝜋 𝜋 1 1
𝐿. 𝐿: 𝑥 = 0 ⇨ 𝜃 = 0
𝑈. 𝐿: 𝑥 = 4
⇨ 𝑡 = sin ( 4 ) – cos ( 4 ) = − =0
√2 √2
𝜋
𝑈. 𝐿: 𝑥 = 1 ⇨ 𝜃 = 4
𝑠𝑖𝑛𝑥 − 𝑐𝑜𝑠𝑥 = 𝑡 S.O.B 1 (1+𝑥)
∫0 log (1+𝑥 2) 𝑑𝑥
⇨ (𝑠𝑖𝑛𝑥 − 𝑐𝑜𝑠𝑥)2 = 𝑡 2
⇨𝑠𝑖𝑛2 𝑥 + 𝑐𝑜𝑠 2 𝑥 − 2𝑠𝑖𝑛𝑥𝑐𝑜𝑠𝑥 = 𝑡 2
𝜋/4 log(1+𝑡𝑎𝑛𝜃)
⇨1 − 𝑠𝑖𝑛2𝑥 = 𝑡 2 = ∫0 (1+𝑡𝑎𝑛2𝜃)
𝑠𝑒𝑐 2 𝜃𝑑𝜃

𝟏 − 𝒕𝟐 = 𝒔𝒊𝒏𝟐𝒙
𝜋/4
𝐼 = ∫0 log(1 + 𝑡𝑎𝑛𝜃)𝑑𝜃 … … … . . (1)
𝜋/4 𝑠𝑖𝑛𝑥+𝑐𝑜𝑠𝑥
𝐼 = ∫0 9+16𝑠𝑖𝑛2𝑥
𝑑𝑥 𝒂 𝒂

## ∴ ∫ 𝒇(𝒙)𝒅𝒙 = ∫ 𝒇(𝒂 − 𝒙)𝒅𝒙

𝟎 𝟎
0 1
= ∫−1 9+16(1−𝑡 2) 𝑑𝑡
𝜋/4 𝜋
𝐼 = ∫0 log (1 + 𝑡𝑎𝑛 [ − 𝜃]) 𝑑𝜃
0 1 4
= ∫−1 9+16−16𝑡 2 𝑑𝑡
𝜋/4 1−𝑡𝑎𝑛𝜃
𝐼 = ∫0 log (1 + ) 𝑑𝜃
1+𝑡𝑎𝑛𝜃
0 1
= ∫−1 25−16𝑡 2 𝑑𝑡
𝜋/4 1+𝑡𝑎𝑛𝜃+1−𝑡𝑎𝑛𝜃
𝐼 = ∫0 log ( 1+𝑡𝑎𝑛𝜃
) 𝑑𝜃
0 1
= ∫−1 (5)2−(4𝑡)2 𝑑𝑡 𝜋/4 2
𝐼 = ∫0 log (1+𝑡𝑎𝑛𝜃 ) 𝑑𝜃
𝟏 𝟏 𝒂+𝒙
∴ ∫ 𝒂𝟐−𝒙𝟐 𝒅𝒙 = 𝟐𝒂 𝐥𝐨𝐠 |𝒂−𝒙| + 𝒄
𝐥𝐨𝐠( 𝒂/𝒃) = 𝐥𝐨𝐠 𝒂 − 𝐥𝐨𝐠 𝒃

1 5+4𝑡 0
[ log |4−5𝑡 |] 𝜋/4 𝜋/4
2[5]
= −1
𝐼 = ∫0 log 2𝑑𝜃 − ∫0 log(1 + tanθ) 𝑑𝜃
4
𝜋/4
=
1
[log |
5+0
| − log |
5−4
|] 𝐼 + 𝐼 = ∫0 log 2𝑑𝜃
40 5−0 5+4
𝜋/4
1 1 𝐥𝐨𝐠 𝟏 = 𝟎 2𝐼 = log 2 ∫0 (1)𝑑𝜃
= 40 [log 1 − log 9 ]
𝜋/4
1 1 2𝐼 = log 2[𝜃]0
= 40 [0 − log 3−2 ] = 40 [2 log 3]
𝜋
1 2𝐼 = log 2 [ 4 − 0]
= 20 log 3
𝜋
𝐼 = 8 log 2

## Laq Q.No 23 Definite integrals

1
Aims Tutorial MATHEMATICS-IIB
𝝅 𝒙.𝒔𝒊𝒏𝒙 𝝅 𝒙
3. ∫𝟎 𝒅𝒙 4. ∫𝟎 𝟏+𝒔𝒊𝒏𝒙
𝒅𝒙
𝟏+𝒔𝒊𝒏𝒙
Sol: Sol:
𝜋 𝑥.𝑠𝑖𝑛𝑥 𝜋 𝑥
𝐼= ∫0 𝑑𝑥 𝐼 = ∫0 1+𝑠𝑖𝑛𝑥
𝑑𝑥
1+𝑠𝑖𝑛𝑥

𝒂 𝒂 𝒂 𝒂
∴ ∫𝟎 𝒇(𝒙)𝒅𝒙 = ∫𝟎 𝒇(𝒂 − 𝒙)𝒅𝒙 ∴ ∫𝟎 𝒇(𝒙)𝒅𝒙 = ∫𝟎 𝒇(𝒂 − 𝒙)𝒅𝒙

𝜋 (𝜋−𝑥).sin(𝜋−𝑥) 𝜋 (𝜋−𝑥)
𝐼 = ∫0 𝑑𝑥 𝐼 = ∫0 1+sin(𝜋−𝑥)
𝑑𝑥
1+sin(𝜋−𝑥)

𝜋 (𝜋−𝑥).𝑠𝑖𝑛𝑥 𝜋 (𝜋−𝑥)
𝐼 = ∫0 𝑑𝑥 𝐼 = ∫0 1+𝑠𝑖𝑛𝑥
𝑑𝑥
1+𝑠𝑖𝑛𝑥

𝜋 𝜋
𝜋
𝜋𝑠𝑖𝑛𝑥 𝜋
𝑥. 𝑠𝑖𝑛𝑥 𝜋 𝑥
𝐼=∫ 𝑑𝑥 − ∫ 𝑑𝑥 𝐼=∫ 𝑑𝑥 − ∫ 𝑑𝑥
0 1 + 𝑠𝑖𝑛𝑥 0 1 + 𝑠𝑖𝑛𝑥 0 1 + 𝑠𝑖𝑛𝑥 0 1 + 𝑠𝑖𝑛𝑥

𝜋 𝑠𝑖𝑛𝑥 𝜋 1
𝐼 + 𝐼 = 𝜋 ∫0 𝑑𝑥 𝐼 + 𝐼 = 𝜋 ∫0 1+𝑠𝑖𝑛𝑥
𝑑𝑥
1+𝑠𝑖𝑛𝑥

𝜋 𝑠𝑖𝑛𝑥(1−𝑠𝑖𝑛𝑥) 𝜋 (1−𝑠𝑖𝑛𝑥)
2𝐼 = 𝜋 ∫0 𝑑𝑥 2𝐼 = 𝜋 ∫0 (1+𝑠𝑖𝑛𝑥)(1−𝑠𝑖𝑛𝑥)
𝑑𝑥
(1+𝑠𝑖𝑛𝑥)(1−𝑠𝑖𝑛𝑥)

𝜋 1−𝑠𝑖𝑛𝑥
𝜋 𝑠𝑖𝑛𝑥−𝑠𝑖𝑛2𝑥 2𝐼 = 𝜋 ∫0 𝑑𝑥
2𝐼 = 𝜋 ∫0 𝑑𝑥 (1−𝑠𝑖𝑛2𝑥)
(1−𝑠𝑖𝑛2 𝑥)

𝜋 1−𝑠𝑖𝑛𝑥
𝜋 𝑠𝑖𝑛𝑥−𝑠𝑖𝑛2𝑥 2𝐼 = 𝜋 ∫0 𝑑𝑥
2𝐼 = 𝜋 ∫0 𝑑𝑥 (𝑐𝑜𝑠 2 𝑥)
(𝑐𝑜𝑠 2 𝑥)

𝜋 1 𝑠𝑖𝑛𝑥 1
𝜋 𝑠𝑖𝑛𝑥 1 𝑠𝑖𝑛2𝑥 2𝐼 = 𝜋 ∫0 [ − 𝑐𝑜𝑠𝑥 . 𝑐𝑜𝑠𝑥 ] 𝑑𝑥
2𝐼 = 𝜋 ∫0 [ . − 𝑐𝑜𝑠2 𝑥 ] 𝑑𝑥 𝑐𝑜𝑠 2 𝑥
𝑐𝑜𝑠𝑥 𝑐𝑜𝑠𝑥
𝜋
𝜋 2 2𝐼 = 𝜋 ∫0 [𝑠𝑒𝑥 2 𝑥 − 𝑡𝑎𝑛𝑥. 𝑠𝑒𝑐𝑥]𝑑𝑥
2𝐼 = 𝜋 ∫0 [𝑡𝑎𝑛𝑥. 𝑠𝑒𝑐𝑥 − 𝑡𝑎𝑛 𝑥]𝑑𝑥

𝜋 𝜋 ∫ 𝒔𝒆𝒙𝟐 𝒙 𝒅𝒙 = 𝒕𝒂𝒏𝒙 + 𝒄
2𝐼 = 𝜋 ∫0 𝑡𝑎𝑛𝑥. 𝑠𝑒𝑐𝑥. 𝑑𝑥 - 𝜋 ∫0 𝑡𝑎𝑛2 𝑥 𝑑𝑥 ∫ 𝒕𝒂𝒏𝒙. 𝒔𝒆𝒄𝒙. 𝒅𝒙 = 𝒔𝒆𝒄𝒙 + 𝒄

## ∫ 𝒕𝒂𝒏𝒙. 𝒔𝒆𝒄𝒙. 𝒅𝒙 = 𝒔𝒆𝒄𝒙 + 𝒄

𝜋 𝜋
𝜋 𝜋 2𝐼 = 𝜋[𝑡𝑎𝑛𝑥]0 - 𝜋[𝑠𝑒𝑐𝑥]0
2𝐼 = 𝜋[𝑠𝑒𝑐𝑥]0 - 𝜋 ∫0 (𝑠𝑒𝑥 2 𝑥 − 1)𝑑𝑥

∫ 𝒔𝒆𝒙𝟐 𝒙 𝒅𝒙 = 𝒕𝒂𝒏𝒙 + 𝒄
2𝐼 = 𝜋[𝑡𝑎𝑛𝜋 − 𝑡𝑎𝑛0]- 𝜋[𝑠𝑒𝑐𝜋 − 𝑠𝑒𝑐0]

𝜋 𝜋 2𝐼 = 𝜋[0 − 0] - 𝜋[−1 − 1]
2𝐼 = 𝜋[𝑠𝑒𝑐𝜋 − 𝑠𝑒𝑐0] - 𝜋[𝑡𝑎𝑛𝑥] 0 -𝜋[𝑥]0
2𝐼 = 2𝜋
2𝐼 = 𝜋[−1 − 1] - 𝜋[0 − 0] + 𝜋[𝜋 − 0]
𝐼 =𝜋
2𝐼 = −2𝜋 +𝜋 2
𝜋2
𝐼= 2
−𝜋

## Laq Q.No 23 Definite integrals

2
Aims Tutorial MATHEMATICS-IIB
𝝅 𝒙.𝒔𝒊𝒏𝒙 𝝅 𝒙.𝒔𝒊𝒏𝟑 𝒙
5. ∫𝟎 𝒅𝒙 6. ∫𝟎 𝒅𝒙
𝟏+𝒄𝒐𝒔𝟐𝒙 𝟏+𝒄𝒐𝒔𝟐𝒙
𝑆𝑜𝑙: 𝑆𝑜𝑙:
𝜋 𝑥.𝑠𝑖𝑛𝑥 𝜋 𝒙.𝒔𝒊𝒏𝟑 𝒙
𝐼= ∫0 1+𝑐𝑜𝑠 2 𝑥
𝑑𝑥 𝐼 = ∫0 𝑑𝑥
𝟏+𝒄𝒐𝒔𝟐 𝒙

𝒂 𝒂
∴ ∫𝟎 𝒇(𝒙)𝒅𝒙 = ∫𝟎 𝒇(𝒂 − 𝒙)𝒅𝒙 𝒂 𝒂
∴ ∫𝟎 𝒇(𝒙)𝒅𝒙 = ∫𝟎 𝒇(𝒂 − 𝒙)𝒅𝒙

𝜋 (𝜋−𝑥).sin(𝜋−𝑥)
𝐼 = ∫0 𝑑𝑥 𝜋 (𝜋−𝑥).𝒔𝒊𝒏𝟑 (𝜋−𝑥)
1+𝑐𝑜𝑠 2 (𝜋−𝑥) 𝐼 = ∫0 𝑑𝑥
1+𝑐𝑜𝑠 2 (𝜋−𝑥)

𝜋 (𝜋−𝑥).𝑠𝑖𝑛𝑥
𝐼 = ∫0 1+𝑐𝑜𝑠 2 𝑥
𝑑𝑥 𝜋 (𝜋−𝑥).𝒔𝒊𝒏𝟑 𝑥
𝐼 = ∫0 1+𝑐𝑜𝑠 2 𝑥
𝑑𝑥
𝜋 𝜋
𝜋𝑠𝑖𝑛𝑥 𝑥. 𝑠𝑖𝑛𝑥 𝜋 𝜋
𝐼=∫ 2
𝑑𝑥 − ∫ 𝑑𝑥 𝜋𝑠𝑖𝑛3 𝑥 𝑥. 𝑠𝑖𝑛3 𝑥
0 1 + 𝑐𝑜𝑠 𝑥 0 1 + 𝑐𝑜𝑠 2 𝑥 𝐼=∫ 𝑑𝑥 − ∫ 𝑑𝑥
0 1 + 𝑐𝑜𝑠 2 𝑥 0 1 + 𝑐𝑜𝑠 2 𝑥
𝜋 𝑠𝑖𝑛𝑥
𝐼 + 𝐼 = 𝜋 ∫0 1+𝑐𝑜𝑠 2 𝑥
𝑑𝑥 𝜋 𝒔𝒊𝒏𝟑 𝑥 𝜋 𝒔𝒊𝒏𝟑 𝑥
𝐼 + 𝐼 = 𝜋 ∫0 1+𝑐𝑜𝑠 2 𝑥
𝑑𝑥 = 𝜋 ∫0 1+𝑐𝑜𝑠 2 𝑥
𝑑𝑥
𝜋 𝑠𝑖𝑛𝑥
2𝐼 = 𝜋 ∫0 1+𝑐𝑜𝑠 2 𝑥
𝑑𝑥
𝑙𝑒𝑡 𝑐𝑜𝑠𝑥 = 𝑡 ⇨ −𝑠𝑖𝑥𝑑𝑥 = 𝑑𝑡
𝑜𝑟
𝑙𝑒𝑡 𝑐𝑜𝑠𝑥 = 𝑡 ⇨ −𝑠𝑖𝑥𝑑𝑥 = 𝑑𝑡 𝒔𝒊𝒏𝒙𝒅𝒙 = −𝒅𝒕
𝑜𝑟 𝑠𝑖𝑛2 𝑥 = 1 − 𝑐𝑜𝑠 2 𝑥 = 1 − 𝑡 2
𝒔𝒊𝒏𝒙𝒅𝒙 = −𝒅𝒕
𝒔𝒊𝒏𝟑 𝑥 = −(1 − 𝑡 2 )𝑑𝑡

𝐿. 𝐿: 𝑥 = 0 ⇨ 𝑡 = 1 ; 𝑈. 𝐿: 𝑥 = 𝜋 ⇨ 𝑡 = −1 𝐿. 𝐿: 𝑥 = 0 ⇨ 𝑡 = 1 ; 𝑈. 𝐿: 𝑥 = 𝜋 ⇨ 𝑡 = −1

−1 −1
⇨2𝐼 = 𝜋 ∫1 1+𝑡 2
𝑑𝑡
−1 −(1−𝑡 2 )
⇨2𝐼 = 𝜋 ∫1 𝑑𝑡
1 1+𝑡 2
1
⇨2𝐼 = 𝜋 ∫−1 1+𝑡 2
𝑑𝑡
−1 𝑡 2 −1 −1 𝑡 2+1−2
⇨2𝐼 = 𝜋 ∫1 𝑑𝑡 = 𝜋 ∫1 𝑑𝑡
1+𝑡 2 1+𝑡 2
2𝐼 = 𝜋[tan−1 𝑡] −1 2
⇨2𝐼 = 𝜋 ∫1 [1 − ] 𝑑𝑡
1+𝑡 2
2𝐼 = 𝜋[tan−1 (1) − tan−1 (−1)]

−1
2𝐼 = 𝜋[t − 2tan−1 𝑡]1
𝜋 𝜋
2𝐼 = 𝜋 [ 4 + 4 ]
2𝐼 = 𝜋[−1 − 1] − 2𝜋[tan−1 (−1) − tan−1 (1)]
𝜋 𝜋
2𝐼 = 𝜋 [2. ] = 𝜋 [. ]
4 4
𝜋 𝜋
2𝐼 = −2𝜋 + 2𝜋 [ 4 + 4 ]
𝜋2
𝐼=
4
𝜋
2𝐼 = −2𝜋 + 2𝜋 [ 2 ]
𝜋2 𝜋
𝐼 = −𝜋 + = (𝜋 − 2)
2 2
Laq Q.No 23 Definite integrals
3
Aims Tutorial MATHEMATICS-IIB

𝝅/𝟐 𝒙 𝜋 1 1
7. ∫𝟎 𝒄𝒐𝒔𝒙+𝒔𝒊𝒏𝒙
𝒅𝒙 𝐼 = ∫0 𝑑𝑡
2 −[(𝑡−1)2 −(√2)2 ]

𝑠𝑜𝑙:
𝜋/2 𝑥 𝜋 1 1
𝐼 = ∫0 𝑐𝑜𝑠𝑥+𝑠𝑖𝑛𝑥
𝑑𝑥 𝐼 = ∫0 𝑑𝑡
2 [(√2)2 −(𝑡−1)2 ]

𝒂 𝒂
∴ ∫𝟎 𝒇(𝒙)𝒅𝒙 = ∫𝟎 𝒇(𝒂 − 𝒙)𝒅𝒙
𝟏 𝟏 𝒂+𝒙
∴ ∫ 𝒂𝟐−𝒙𝟐 𝒅𝒙 = 𝟐𝒂 𝐥𝐨𝐠 |𝒂−𝒙| + 𝒄

𝜋
𝜋/2 ( −𝑥)
2
𝐼= ∫0 𝜋 𝜋 𝑑𝑥
cos( −𝑥)+sin( −𝑥)
2 2
1
𝜋 1 √2+𝑡−1
2𝐼 = )
[log | |0 ]
𝜋 2 2(√2 √2−𝑡+1
𝜋/2 ( −𝑥)
2
𝐼 = ∫0 𝑑𝑥
𝑠𝑖𝑛𝑥+𝑐𝑜𝑠𝑥
𝜋 1 √2+1−1 √2−1
𝐼= [log | | − log | |]
2 2√2 √2−1+1 √2+1
𝜋
𝜋/2 𝜋/2
2 𝑥
=∫ 𝑑𝑥 − ∫ 𝑑𝑥 𝜋 1 √2+1
0 𝑐𝑜𝑠𝑥 + 𝑠𝑖𝑛𝑥 0 𝑐𝑜𝑠𝑥 + 𝑠𝑖𝑛𝑥 𝐼= [log|1| + log | |]
2 2√2 √2−1

𝜋 𝜋/2 1 𝜋 1 √2+1
𝐼 + 𝐼 = 2 ∫0 𝑑𝑥 𝐼= log | |
𝑐𝑜𝑠𝑥+𝑠𝑖𝑛𝑥 2 2√2 √2−1

𝜋 𝜋/2 1
2𝐼 = 2 ∫0 𝑑𝑥 𝜋 1 (√2+1)(√2+1)
𝑐𝑜𝑠𝑥+𝑠𝑖𝑛𝑥 𝐼= log | |
2 2√2 (√2−1)(√2+1)
𝑥
Let t= 𝑡𝑎𝑛 ( 2) ;
𝜋 1 (√2+1)2
𝑑𝑥=
2𝑑𝑡
; 𝐼= 2 2√2
log 2
1+𝑡 2 √2 −12
1−𝑡 2
cos 𝑥 = 1+𝑡 2
2 (√2+1)
𝑠𝑖𝑛𝑥=
2𝑡 𝐼 = 2√2 log 2−1
1+𝑡 2

𝜋
𝐼 = 2√2 log(√2 + 1)

𝜋 1 1 2𝑑𝑡
2𝐼 = ∫0 1−𝑡2
( )
2 2𝑡
( 2 )+( 2 ) 1+𝑡 2
1+𝑡 1+𝑡

𝜋 1 1 2𝑑𝑡
2𝐼 = ∫0 1−𝑡2+2𝑡
( )
2 [ ] 1+𝑡 2
1+𝑡2

𝜋 1 1
2𝐼 = 2 ∫0 𝑑𝑡
2 −(𝑡 2 −2𝑡−1)

𝜋 1 1
𝐼 = ∫0 𝑑𝑡
2 −[𝑡 2 −2𝑡+(1)2 −(1)2 −1]

## Laq Q.No 23 Definite integrals

4
Aims Tutorial MATHEMATICS-IIB

𝝅/𝟐 𝑠𝑖𝑛2𝑥 1 1
8. ∫𝟎 𝒄𝒐𝒔𝒙+𝒔𝒊𝒏𝒙
𝒅𝒙 𝐼 = ∫0 𝑑𝑡
−[(𝑡−1)2 −(√2)2 ]

𝑠𝑜𝑙:
𝜋/2 𝑠𝑖𝑛2 𝑥 1 1
𝐼 = ∫0 𝑑𝑥 … (1) 𝐼 = ∫0 𝑑𝑡
𝑐𝑜𝑠𝑥+𝑠𝑖𝑛𝑥 [(√2)2 −(𝑡−1)2 ]

𝒂 𝒂
∴ ∫𝟎 𝒇(𝒙)𝒅𝒙 = ∫𝟎 𝒇(𝒂 − 𝒙)𝒅𝒙 𝟏 𝟏 𝒂+𝒙
∴ ∫ 𝒂𝟐−𝒙𝟐 𝒅𝒙 = 𝟐𝒂 𝐥𝐨𝐠 |𝒂−𝒙| + 𝒄

𝜋
𝜋/2 𝑠𝑖𝑛2( −𝑥)
2
𝐼 = ∫0 𝜋 𝜋 𝑑𝑥
cos( −𝑥)+sin( −𝑥)
2 2 1
1 √2+𝑡−1
2𝐼 = )
[log | |0 ]
2(√2 √2−𝑡+1
𝜋/2 𝑐𝑜𝑠 2 𝑥
𝐼 = ∫0 𝑠𝑖𝑛𝑥+𝑐𝑜𝑠𝑥
𝑑𝑥 … (2)
1 √2+1−1 √2−1
𝐼= [log | | − log | |]
𝐴𝑑𝑑𝑖𝑛𝑔 (1) & (2) 2√2 √2−1+1 √2+1

𝜋/2
𝑠𝑖𝑛2 𝑥 𝜋/2
𝑐𝑜𝑠2 𝑥 1
𝐼 = 2√2 [log|1| + log |
√2+1
|]
=∫ 𝑑𝑥 + ∫ 𝑑𝑥 √2−1
0 𝑐𝑜𝑠𝑥 + 𝑠𝑖𝑛𝑥 0 𝑐𝑜𝑠𝑥 + 𝑠𝑖𝑛𝑥

1 √2+1
𝐼= log | |
𝜋/2 𝑠𝑖𝑛2 𝑥+𝑐𝑜𝑠 2 𝑥 2√2 √2−1
𝐼+𝐼 = ∫0 𝑑𝑥
𝑐𝑜𝑠𝑥+𝑠𝑖𝑛𝑥
1 (√2+1)(√2+1)
𝜋/2 1 𝐼= log | |
2𝐼 = ∫0 𝑐𝑜𝑠𝑥+𝑠𝑖𝑛𝑥
𝑑𝑥 2√2 (√2−1)(√2+1)

1 (√2+1)2
Let t= 𝑡𝑎𝑛 ( 2) ;
𝑥 𝐼 = 2√2 log 2
√2 −12
2𝑑𝑡
𝑑𝑥= 1+𝑡 2
;
2 (√2+1)
1−𝑡 2 𝐼 = 2√2 log
cos 𝑥 = 1+𝑡 2 2−1
2𝑡
𝑠𝑖𝑛𝑥=
1+𝑡 2 1
𝐼= log(√2 + 1)
√2

1 1 2𝑑𝑡
2𝐼 = ∫0 1−𝑡2
( )
2𝑡
( 2 )+( 2 ) 1+𝑡 2
1+𝑡 1+𝑡

1 1 2𝑑𝑡
2𝐼 = ∫0 1−𝑡2 +2𝑡
( )
[ ] 1+𝑡 2
1+𝑡2

1 1
2𝐼 = 2 ∫0 𝑑𝑡
−(𝑡 2 −2𝑡−1)

1 1
𝐼 = ∫0 𝑑𝑡
−[𝑡 2 −2𝑡+(1)2 −(1)2 −1]
Laq Q.No 23 Definite integrals
5
Aims Tutorial MATHEMATICS-IIB

𝟗 𝟏
9. ∫𝟑
𝟕

𝟕−𝒙
𝒅𝒙. 10. ∫𝟒 𝒅𝒙.
𝒙−𝟑 √(𝟗−𝒙)(𝒙−𝟒)

𝑆𝑜𝑙: 𝑆𝑜𝑙:
𝑙𝑒𝑡 𝑥 = 3𝑐𝑜𝑠 2 𝜃 + 7𝑠𝑖𝑛2 𝜃 𝑙𝑒𝑡 𝑥 = 4𝑐𝑜𝑠 2 𝜃 + 9𝑠𝑖𝑛2 𝜃
𝑑𝑥 = 8𝑠𝑖𝑛𝜃𝑐𝑜𝑠𝜃. 𝑑𝜃 𝑑𝑥 = 10𝑠𝑖𝑛𝜃𝑐𝑜𝑠𝜃. 𝑑𝜃

𝐿. 𝐿: 𝑥 = 3 ⇨ 𝜃 = 0 𝐿. 𝐿: 𝑥 = 4 ⇨ 𝜃 = 0

𝜋
𝑈. 𝐿: 𝑥 = 7 ⇨ 𝜃 =
𝜋 𝑈. 𝐿: 𝑥 = 9 ⇨ 𝜃 = 2
2
7 − 𝑥 = 7 − 3𝑐𝑜𝑠 𝜃 − 7𝑠𝑖𝑛 𝜃 2 2 9 − 𝑥 = 9 − 4𝑐𝑜𝑠 2 𝜃 − 9𝑠𝑖𝑛2 𝜃
= 7(1 − 𝑠𝑖𝑛2 𝜃) − 3𝑐𝑜𝑠 2 𝜃 = 9(1 − 𝑠𝑖𝑛2 𝜃) − 3𝑐𝑜𝑠 2 𝜃
= 7(𝑐𝑜𝑠 2 𝜃) − 3𝑐𝑜𝑠 2 𝜃 = 9(𝑐𝑜𝑠 2 𝜃) − 4𝑐𝑜𝑠 2 𝜃
= 4𝑐𝑜𝑠 2 𝜃 = 5𝑐𝑜𝑠 2 𝜃

## = 7𝑠𝑖𝑛2 𝜃 − 3(𝑠𝑖𝑛2 𝜃) = 9𝑠𝑖𝑛2 𝜃 − 4(𝑠𝑖𝑛2 𝜃)

= 4𝑠𝑖𝑛2 𝜃 = 5𝑠𝑖𝑛2 𝜃
𝟗 𝟏
7 7−𝑥 ∫𝟒 𝒅𝒙.
∫3 √ 𝑑𝑥 √(𝟗−𝒙)(𝒙−𝟒)
𝑥−3 𝜋/2 1
= ∫0 √5𝑐𝑜𝑠 2 𝜃5𝑠𝑖𝑛2 𝜃
10𝑠𝑖𝑛𝜃𝑐𝑜𝑠𝜃𝑑𝜃
𝜋/2 4𝑐𝑜𝑠 2𝜃
= ∫0 √ 8𝑠𝑖𝑛𝜃𝑐𝑜𝑠𝜃𝑑𝜃
4𝑠𝑖𝑛2𝜃
𝜋/2 1
== ∫0 10𝑠𝑖𝑛𝜃𝑐𝑜𝑠𝜃𝑑𝜃
5𝑠𝑖𝑛𝜃𝑐𝑜𝑠𝜃
𝜋/2
= 8 ∫0 𝑐𝑜𝑠 2 𝜃 𝑑𝜃

## 𝝅/𝟐 𝒏−𝟏 𝐧−𝟑 𝐧−𝟓 𝛑 𝝅/𝟐

∫𝟎 𝒄𝒐𝒔𝒏 𝒙 𝒅𝒙 = . . … 𝑰 = 𝟐 ∫𝟎 𝟏 𝒅𝒙
𝒏 𝐧−𝟐 𝐧−𝟒 𝟐

1 π 𝜋/2 2π
= 8. (2) 2 = 2π = 2[𝑥]0 = 2

## Laq Q.No 23 Definite integrals

6
Aims Tutorial MATHEMATICS-IIB
𝒃 𝝅
11. 𝑬𝒗𝒂𝒍𝒖𝒂𝒕𝒆 ∫𝒂 √(𝒙 − 𝒂)(𝒙 − 𝒃)𝒅𝒙 12. ∫𝟎 𝒙. 𝒔𝒊𝒏𝟕 𝒙𝒄𝒐𝒔𝟔 𝒙 𝒅𝒙
𝑆𝑜𝑙:
𝑏 𝜋
Sol: ∫𝑎 √−(𝑥 − 𝑎)(𝑥 − 𝑏)𝑑𝑥 𝐼 = ∫0 𝑥. 𝑠𝑖𝑛7 𝑥𝑐𝑜𝑠 6 𝑥 𝑑𝑥
𝑎 𝑎
∴ ∫0 𝑓(𝑥)𝑑𝑥 = ∫0 𝑓(𝑎 − 𝑥)𝑑𝑥

𝑏
𝐼 = ∫𝑎 √−[𝑥 2 − (𝑎 + 𝑏)𝑥 + 𝑎𝑏]𝑑𝑥
𝜋
𝐼 = ∫0 (𝜋 − 𝑥)𝑠𝑖𝑛7 (𝜋 − 𝑥)𝑐𝑜𝑠 6 (𝜋 − 𝑥) 𝑑𝑥

𝑏 𝜋
[𝑎 + 𝑏]2 [𝑎 + 𝑏]2 𝐼 = ∫0 (𝜋 − 𝑥)𝑠𝑖𝑛7 𝑥𝑐𝑜𝑠 6 𝑥 𝑑𝑥
= ∫ √− [𝑥 2 − (𝑎 + 𝑏)𝑥 + − + 𝑎𝑏] 𝑑𝑥
4 4
𝑎
𝜋 𝜋
𝐼 = ∫0 𝜋𝑠𝑖𝑛7 𝑥𝑐𝑜𝑠 6 𝑥 𝑑𝑥 -∫0 𝑥𝑠𝑖𝑛 7 𝑥𝑐𝑜𝑠 6 𝑥 𝑑𝑥

𝜋
𝑏 𝑎+𝑏 2 [𝑏−𝑎]2 𝐼 = ∫0 𝜋𝑠𝑖𝑛7 𝑥𝑐𝑜𝑠 6 𝑥 𝑑𝑥 −𝐼
= ∫𝑎 √− [[𝑥 − 2
] − 4
] 𝑑𝑥

𝜋
𝐼 + 𝐼 = 𝜋 ∫0 𝑠𝑖𝑛7 𝑥𝑐𝑜𝑠 6 𝑥 𝑑𝑥

𝑏 𝑏−𝑎 2 𝑎+𝑏 2 𝟐𝒂 𝒂
= ∫𝑎 √[[ 2
] − [𝑥 − 2
] ] 𝑑𝑥 ∴ ∫𝟎 𝒇(𝒙)𝒅𝒙 = 𝟐 ∫𝟎 𝒇(𝒙)𝒅𝒙

𝜋/2
2𝐼 = 2𝜋 ∫0 𝑠𝑖𝑛7 𝑥𝑐𝑜𝑠 6 𝑥 𝑑𝑥
𝐱 𝐚𝟐 𝒙
∴ ∫ √𝒂𝟐 − 𝒙𝟐 𝒅𝒙 = 𝟐 √𝒂𝟐 − 𝒙𝟐 + 𝐬𝐢𝐧−𝟏 (𝒂) + 𝒄
𝟐
𝜋/2
𝐼 = 𝜋 ∫0 𝑠𝑖𝑛7 𝑥𝑐𝑜𝑠 6 𝑥 𝑑𝑥

𝐚+𝐛 𝐚+𝐛 𝑏
[𝐱− ] [𝐛−𝐚]𝟐 (𝐱− ) 𝝅/𝟐
𝐼=[ 𝟐
√(𝒂 − 𝒙)(𝒃 − 𝒙) + 𝐬𝐢𝐧 −𝟏
𝒃−𝒂
𝟐
] ∫𝟎 𝒄𝒐𝒔𝒏 𝒙 𝒔𝒊𝒏𝒎 𝒙 𝒅𝒙 =
𝟐 𝟒.𝟐
𝟐 𝑎 (𝒏 − 𝟏)(𝒏 − 𝟑)(𝒏 − 𝟓) … (𝒎 − 𝟏)(𝒎 − 𝟑) …
(𝒎 + 𝒏)(𝒎 + 𝒏 − 𝟐)(𝒎 + 𝒏 − 𝟒) …

𝐚+𝐛 𝐚+𝐛
[𝐛− ] [𝐛−𝐚]𝟐 (𝐛− )
=[ 𝟐
√(𝒂 − 𝒃)(𝒃 − 𝒃) + 𝐬𝐢𝐧−𝟏 𝟐
] 6.4.2.5.3.1
𝟐 𝟒.𝟐 𝒃−𝒂
𝟐 𝐼 = 𝜋 13.11.9.7.5.3.1
𝐚+𝐛 𝐚+𝐛
[𝐚− ] [𝐛−𝐚]𝟐 (𝐚− )
−[ 𝟐
√(𝒂 − 𝒂)(𝒃 − 𝒂) + 𝐬𝐢𝐧−𝟏 𝒃−𝒂
𝟐
] 6.4.2
𝟐 𝟒.𝟐
𝟐 𝐼 = 𝜋 13.11.9.7

16𝜋
−𝟏 (𝐛−𝐚) −𝟏 (𝐚−𝐛) 𝐼 = 3003
[𝐛−𝐚]𝟐 [𝐛−𝐚]𝟐
=[ 𝐬𝐢𝐧 𝟐
𝒃−𝒂 ] −[ 𝐬𝐢𝐧 𝟐
𝒃−𝒂 ]
𝟖 𝟖
𝟐 𝟐

−𝟏 −𝟏
[𝐛−𝐚]𝟐 [𝐛−𝐚]𝟐
=[ 𝐬𝐢𝐧 𝟏] −[ 𝐬𝐢𝐧 (−𝟏)]
𝟖 𝟖

=[ 𝟖
( )]+[
𝟐 𝟖
( )] =
𝟐 𝟖

## Laq Q.No 23 Definite integrals

7
Aims Tutorial MATHEMATICS-IIB

## 13. Find the area enclosed by the curves

𝒚𝟐 = 𝟒𝒂𝒙 𝒂𝒏𝒅 𝒙𝟐 = 𝟒𝒃𝒚 . 14. Find the area enclosed by the curves
Sol: 𝒚 = 𝟒 − 𝟐𝒙 𝒂𝒏𝒅 𝒚 = 𝒙𝟐 − 𝟓𝒙 .
Given eq’’n 𝑺𝒐𝒍:
𝑦 2 = 4𝑎𝑥 ⇨ 𝑦 = √4𝑎𝑥 … (1) Given eq’’n

𝒙𝟐 𝑦 = 4 − 2𝑥 … . . (1)
𝒙𝟐 = 𝟒𝒃𝒚 ⇨ 𝒚 = … . . (2)
4𝑏 𝑦 = 𝑥 2 − 5𝑥 … (1)
𝑠𝑜𝑙𝑣𝑖𝑛𝑔 (1)𝑎𝑛𝑑 (2)
𝑠𝑜𝑙𝑣𝑖𝑛𝑔 (1)𝑎𝑛𝑑 (2)
𝑥 2 − 5𝑥=4 − 2𝑥
⇨𝑥 2 - 3𝑥 − 4 = 0
𝒙𝟐
√4𝑎𝑥 = 4𝑏
S.O.B ⇨𝑥 2 +1x- 4𝑥 − 4 = 0

𝒙𝟒 ⇨𝑥(𝑥 + 1) − 4(𝑥+1) = 0
⇨4𝑎𝑥 = 16𝑏2
𝑥 = 4 𝑜𝑟 𝑥 = −1

⇨ 64𝑎𝑏2 𝑥 = 𝒙𝟒 ⇨ 64𝑎𝑏2 𝑥 − 𝒙𝟒 = 0 4
Required Area =∫−1[(1)— (2)] 𝑑𝑥
4
⇨ 𝑥(64𝑎𝑏2 − 𝒙𝟑 ) = 0 =∫−1[4 − 2𝑥 − 𝑥 2 + 5𝑥] 𝑑𝑥
4
= ∫−1[4 + 3𝑥 − 𝑥 2 ] 𝑑𝑥
𝑥 = 0 𝑜𝑟 𝑥 3 = 64𝑎𝑏2 3𝑥 2 𝑥3
4
= [4𝑥 + 2
− 3 −1
]
1/3 2/3
⇨𝑥 = 4𝑎 𝑏 =𝑢
3 1
= 4[4 + 1] + 2 [42 − (−1)2 ]- 3 [43 − (−1)3 ]
3 1
𝑢 = 20 + 2 (16 − 1) − 3 (64 + 1)
Required Area =∫0 [(1)— (2)] 𝑑𝑥
45 65
𝑢 𝒙𝟐 = 20 + 2
− 3
=∫0 [√4𝑎𝑥 − ] 𝑑𝑥
4𝑏
120+135−135
𝑢 𝑥2
= 6
= ∫0 [2√𝑎𝑥1/2 − 4𝑏] 𝑑𝑥 125
= 6
𝑠𝑞. 𝑢𝑛𝑖𝑡𝑠
𝑢
2√𝑎𝑥 3/2 𝑥3
=[ 3/2
− 4𝑏3]
0

4 1
= 3 √𝑎[𝑢3/2 − 02 ]- 12 [𝑢3 − 03 ]

3
1 2 2 3
4 1
= 3 √𝑎 [[4𝑎 𝑏 ] − 02 ] - 12 [[4𝑎1/3 𝑏2/3 ] − 03 ]
3 3

4 1
= 3 [8𝑎𝑏] − [64𝑎𝑏2 ]
12𝑏

= 3
− 3
= 3
𝑠𝑞. 𝑢𝑛𝑖𝑡𝑠

## Laq Q.No 23 Definite integrals

8
Aims Tutorial MATHEMATICS-IIB

15. Find the area enclosed by the curves 16. Find the area enclosed by the curves
𝒚𝟐 = 𝟒𝒙 𝒂𝒏𝒅 𝒚𝟐 = 𝟒(𝟒 − 𝒙) . 𝒚 = 𝟐 − 𝒙𝟐 𝒂𝒏𝒅 𝒚 = 𝒙𝟐 .
Sol: 𝑺𝒐𝒍:
Given eq’’n Given eq’’n
𝑦 2 = 4𝑥 ⇨ 𝑦 = √4𝑥 … (1)
𝒚 = 𝟐 − 𝒙𝟐 … . . (1)
𝒚𝟐 = 𝟒(𝟒 − 𝒙) ⇨ 𝒚 = √4(4 − 𝑥) … . . (2) 𝑦 = 𝑥 2 … (1)
𝑠𝑜𝑙𝑣𝑖𝑛𝑔 (1)𝑎𝑛𝑑 (2)
𝑠𝑜𝑙𝑣𝑖𝑛𝑔 (1)𝑎𝑛𝑑 (2) 2 − 𝑥2 = 𝑥2
2 = 2𝑥 2
4𝑥 = 𝟒(𝟒 − 𝒙) 𝑥2 = 1
𝑥 = ±1
⇨𝑥 = 4 − 𝑥 ∴ 𝑥 = 1 𝑜𝑟 𝑥 = −1

⇨ 2𝑥 = 4
1
𝑥=2 Required Area =∫−1[(1)— (2)] 𝑑𝑥
Sub x=2 in (1) 1
=∫−1[2 − 𝑥 2 − 𝑥 2 ] 𝑑𝑥
𝑦 2 = 4𝑥 = 4(2) = 8 1
= ∫−1[2 − 2𝑥 2 ] 𝑑𝑥
𝑦 = √8 = ±2√2
1
𝑥3
Two parabolas are symmetric about X-axis = [2𝑥 − 2 ]
2 4 3 −1
Required Area =2 [∫0 (1)𝑑𝑥 + ∫2 (2)𝑑𝑥 ]
2
= 2[1 + 1] − 3 [(1)3 − (−1)3 ]
2 4
=2 [∫0 √4𝑥𝑑𝑥 + ∫2 √4(4 − 𝑥)𝑑𝑥] 2
= 4 − 3 (1 + 1)

2 4
=2 [2 ∫0 𝑥1/2 𝑑𝑥 + 2 ∫2 (4 − 𝑥)1/2 𝑑𝑥 ] = 4−3 =
4 12−4
3
8
2 4
= 3 𝑠𝑞. 𝑢𝑛𝑖𝑡
𝑥 3/2 (4−𝑥)3/2
=4 [ 3/2 ] + 4[ −3/2
]
0 2

8 8
= 3 [23/2 − 03/2 ]- 3 [(4 − 4)3/2 − (4 − 2)3/2 ]

8 8
= 3 [2√2] + 3 [2√2]

16√2 16√2
= 2
+ 2
32√2
= 2
𝑠𝑞. 𝑢𝑛𝑖𝑡𝑠

## Laq Q.No 23 Definite integrals

9
Aims Tutorial MATHEMATICS-IIB

## 17. Show that the area of the region bounded by

𝒙𝟐 𝒚𝟐
𝒂𝟐
+ 𝒃𝟐 = 𝟏 is 𝝅𝒂𝒃.also deduce the area of
the circle 𝒙𝟐 + 𝒚𝟐 = 𝒂𝟐 .
Sol: Given eq’’n of the ellipse
𝑥2 𝑦2
𝑎2
+ 𝑏2 = 1 … … . . (1)

𝑦2 𝑥2
⇨ = 1−
𝑏2 𝑎2

𝑦2 1
⇨ 𝑏2
= 𝑎2 [𝑎2 − 𝑥 2 ]

𝑏2
⇨ 𝑦 2 = 𝑎2 [𝑎2 − 𝑥 2 ]

𝑏
⇨ 𝑦 = ± 𝑎 √𝑎2 − 𝑥 2

## Ellipse is symmetric about both the axes.

Required area =4 area of shaded region

𝑎
Area=∫0 𝑦𝑑𝑥

𝑎𝑏
=4 ∫0 𝑎
√𝑎2 − 𝑥 2 𝑑𝑥

𝑏 𝑎
=4 ∫0 √𝑎2 − 𝑥 2 𝑑𝑥
𝑎

𝐱 𝐚𝟐 𝒙
∴ ∫ √𝒂𝟐 − 𝒙𝟐 𝒅𝒙 = √𝒂𝟐 − 𝒙𝟐 + 𝐬𝐢𝐧−𝟏 ( ) + 𝒄
𝟐 𝟐 𝒂

−𝟏 𝑎
4𝑏 𝐱 𝐚𝟐 𝒙
= [ √𝒂𝟐 − 𝒙𝟐 + 𝐬𝐢𝐧 ( )]
𝑎 𝟐 𝟐 𝒂
0
−𝟏
4𝑏 𝐚 𝐚𝟐 𝒂
= [ √𝒂𝟐 − 𝒂𝟐 + 𝐬𝐢𝐧 ( ) − 𝟎 − 𝟎]
𝑎 𝟐 𝟐 𝒂
𝟐 −𝟏
4𝑏 𝐚
= 𝐬𝐢𝐧 (𝟏)
𝑎 𝟐

2𝑎𝑏𝜋
=
2

= 𝜋𝑎𝑏 𝑠𝑞 𝑢𝑛𝑖𝑡𝑠
If a=b the ellipse becomes a circle
∴Area of the circle 𝒙𝟐 + 𝒚𝟐 = 𝒂𝟐 .
is 𝜋𝑎. 𝑎 = 𝜋𝑎2 𝑠𝑞 . 𝑢𝑛𝑖𝑡𝑠

## Laq Q.No 23 Definite integrals

10
Aims Tutorial MATHEMATICS-IIB

11